Potential risk of BPA and phthalates in commercial water bottles: a minireview - Rouse da Silva Costa; Tatiana Sainara Maia Fernandes; Edmilson de Sousa Almeida; Juliene Tomé Oliveira; Jhonyson Arruda Carvalho Guedes; Guilherme Julião Zocolo; Francisco Wagner de Sousa; Ronaldo Ferreira do Nascimento (IWA Publishing, 2021)
The global water bottling market grows annually. Today, to ensure consumer safety, it is important to verify the possible migration of compounds from bottles into the water contained in them. Potential health risks due to the prevalence of bisphenol A (BPA) and phthalates (PAEs) exposure through water bottle consumption have become an important issue. BPA, benzyl butyl phthalate (BBP), di-n-butyl phthalate (DBP) and di (2-ethylhexyl) phthalate (DEHP) can cause adverse effects on human health. Papers of literature published in English, with BPA, BBP, DBP and DEHP detections during 2017, by 2019 by liquid chromatography and gas chromatography analysis methods were searched. The highest concentrations of BPA, BBP, DBP and DEHP in all the bottled waters studied were found to be 5.7, 12.11, 82.8 and 64.0 μg/L, respectively. DBP was the most compound detected and the main contributor by bottled water consumption with 23.7% of the Tolerable Daily Intake (TDI). Based on the risk assessment, BPA, BBP, DBP and DEHP in commercial water bottles do not pose a serious concern for humans. The average estrogen equivalent level revealed that BPA, BBP, DBP and DEHP in bottled waters may induce adverse estrogenic effects on human health. HIGHLIGHTS DBP was the most compound detected.; An estimated intake of BPA, BBP, DBP and DEHP was far below their TDIs.; The risk assessment of BPA, BBP, DBP and DEHP does not raise serious concern for humans.; The average estrogen equivalent level for BPA, BBP, DBP and DEHP may induce adverse estrogenic effects on human health.; BPA, BBP, DBP and DEHP in bottled water need more accurate data to avoid their effects on human health.;